The missing dimension of knowledge transfer from subsidiaries to headquarters: The case of Oil and Gas companies in CEE region - Velinov, Emil; Gueldenberg, Stefan (Journal of Eastern European and Central Asian Research (JEECAR), 2016)
The paper identifies knowledge management determinants of knowledge transfer from subsidiaries to headquarters in the top Oil & Gas companies in Central and Eastern Europe as their level of innovations, internationalization and economic importance are emerging. The paper sheds a light not only on the process of knowledge transfer parent-subsidiary but via versa as it is critical in the 21st century for better adapting to specific business needs in certain geographical regions. Thus, this reversed knowledge from subsidiaries to headquarters is critical for the given business sector where the level of innovation and amount of R&D investments are enormous. The study argues that the reversed process of knowledge transfers from subsidiary to parent company is positively related to company performance and business diversification. Nowadays the knowledge formed in the subsidiaries of Multinational Corporations (MNCs) is transferred to headquarters by investing in R&D centres, building new exploration and testing sites abroad. In the reversed knowledge transfer process we can identify main challenges, which are very critical to analyse and determine the exact process.